Human Papillomavirus (HPV) Infection in Males: A Need for More Awareness (2019)
Globally, human papillomavirus (HPV) is the most common viral sexually transmitted pathogen, which is significantly associated with high morbidity and mortality in both sexes. Except those vaccinated, virtually all sexually active individuals will be infected with HPV in their lifetime. Although most HPV infections are transient, association with anogenital warts, cervical, penile, and other malignancies have been reported. HPV can be transmitted from one person to another through contact especially during sexual contact including anal, vaginal, or oral. Although HPV infection affects both males and females, its causal association with cervical cancer has made most literature to be mainly on females. In view of its sexual transmissibility and the increasing prevalence of HPV-related malignancies among males worldwide, there is need for more awareness on the infection in males. Most developed countries offer HPV vaccination for girls, but vaccine recommendations for boys are still relatively uncommon especially in developing countries where the burden of HPVrelated malignancies is still very high. The current discourse highlights the need for increased awareness on HPV vaccination among this neglected gender group.